Critical Edition of the Manuscript Tawfīq al-Ilāh fī Sharḥ Fann min al-Ashbāh by Sunbulzāda al-Marʿashī, from His Commentary on the Sixth Principle (al-Ḥudūd Tudraʾ bi-l-Shubuhāt) - جاسم حنان عبيد; حمادي احمد حميد; حمود وقاص فرحان (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
All praise is due to Allah, who taught by the pen, taught man that which he knew not. May peace and blessings be upon our Master Muhammad, and upon his family and all his companions. To proceed: The science of legal maxims is regarded as one of the most noble branches of Islamic law, second only to jurisprudence (fiqh) itself, due to its vital role in organizing subsidiary rulings, linking them to fundamental principles, unifying juristic methodology, facilitating independent reasoning (ijtihad), and structuring legal evidence. The scholars of the Hanafi school accorded this science great importance, producing outstanding works in it. Chief among them is the book "Al-Ashbah wa al-Naza’ir" by the jurist Imam Zayn al-Din Ibn Nujaym al-Misri al-Hanafi (d. 970 AH), which stands as the primary reference for legal maxims not only among the Hanafis but across other schools of law as well. This is due to its precise structure, scholarly craftsmanship, and depth of juristic insight. In this work, Ibn Nujaym addresses various types of legal maxims, categorizing them as foundational and subsidiary, major and minor, and related partial principles. Among the notable scholars who commented on this work in later centuries is Imam Sunbulzade Muhammad Rashid al-Qadi al-Marashi al-Hanafi (d. 1227 AH), a leading figure of the Ottoman Empire and a distinguished authority in the Hanafi school. He authored a valuable commentary on "Al-Ashbah wa al-Naza’ir" which highlights the depth of Ibn Nujaym’s legal understanding, the precision of his language, the clarity of his analysis, and his profound grasp of legal objectives (maqasid). Given the importance and scholarly value of this commentary, we undertook the critical edition of a portion of it—specifically, the second category of general maxims, which Ibn Nujaym introduces with the words: "Now we begin the second type of maxims, which comprises comprehensive principles upon which countless specific rulings are based." This section presents a collection of broad legal maxims that serve as foundations for numerous subsidiary rulings and span vast areas of jurisprudence. The number of verified maxims in this portion is nineteen (19).